A unified web-based framework for Java code analysis and evolutionary automatic test-cases generation - Sofokleous, Anastasis A.; Petsas, Panagiotis; Andreou, Andreas S. (My University, 2010)
This paper describes the implementation and integration of code analysis and testing systems in a unified web-enabled framework. The former analyses basic programs written in Java and constructs the control-flow, data-flow and dependence graph(s), whereas the testing system collaborates with the analysis system to automatically generate and evaluate test-cases with respect to control flow and data flow criteria. The present work describes the design and implementation details of the framework and presents preliminary experimental results.
Keywords: Analysis system; Automatic test; Code analysis; Control flows; Control-flow; Dataflow; Dependence graphs; Edge/condition coverage; Java code analysis; k-Tuples coverage; Test case; Testing systems; Web-based framework; Automatic programming; Computer software; Genetic algorithms; Information systems; Instruments; Java programming language; Data flow analysis